2019
DOI: 10.1177/0145445519850745
|View full text |Cite
|
Sign up to set email alerts
|

Using a Textual Prompt to Teach Multiword Requesting to Two Children With Autism Spectrum Disorder

Abstract: Autism spectrum disorder is characterized by social and communication impairment, but some children appear to have relative strength in areas such as reading printed words. The present study involved two children with limited expressive communication skills, but relatively stronger reading ability. Based on this existing strength, we evaluated a textual prompting procedure for teaching the children to produce multiword spoken requests. The effect of providing textual prompts on production of multiword requests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Roche et al (2019) adopted a low-tech approach in their efforts to teach multiword spoken requests to two children on the autism spectrum. Interestingly, while both children’s speech repertoire was initially limited to single word utterances, a standardized communication assessment revealed that both of these children showed a relative strength with respect to reading printed words.…”
mentioning
confidence: 99%
“…Roche et al (2019) adopted a low-tech approach in their efforts to teach multiword spoken requests to two children on the autism spectrum. Interestingly, while both children’s speech repertoire was initially limited to single word utterances, a standardized communication assessment revealed that both of these children showed a relative strength with respect to reading printed words.…”
mentioning
confidence: 99%